PERAN PEMERINTAH DAN ULAMA DALAM PENGELOLAAN ZAKAT DALAM RANGKA USAHA PENANGGULANGAN KEMISKINAN DAN PENINGKATAN PENDIDIKAN DI INDONESIA - Hayati, Mardhiyah (Universitas Islam Negeri Raden Intan Lampung, 2012)
Abstak: Poverty is the worst conditions experienced by people that the appearance of it was not expected; even almost everyone wanted to avoid it. Adoption is not charity into the state system, causing the Islamic world lost the power to run welfare programs, to solve socioeconomic problems, such as poverty. In the teachings of Islam, Zakat in economics appears to be an alternative instrument for effective poverty reduction, which has many advantages over conventional fiscal instruments that now exist, if the current impact on economic activity is still relatively small, and then this is caused by several things. Spending a minimum expenditure of zakat is to create a more equitable distribution of income that not yet optimum (Necessary but not sufficient condition). Therefore, others expenses necessary to complete the expenditure of zakat such as sadaqah, waqaf and so on. so the impact on income distribution becomes more optimum. Besides the management of zakat which has not been well managed and professionally, as well as low public awareness to tithe correctly. For the role of government and clerics in the management of zakat in order to attempt to reduce poverty and improve education in Indonesia is required. Keywords: government, scholars, Zakat, Poverty Reduction and Improvement of Education